Investigating cognitive mechanisms underlying the corrupt intention: The role of moral disengagement and belief in a just world - Miftahun Najah; Sugiyarta Stanislaus; Sugiariyanti Sugiariyanti; Rulita Hendriyani (Integritas: Jurnal Antikorupsi, 2026)
Corruption is unethical behaviour that undermines integrity, erodes social trust, and causes widespread harm to society. Two psychological constructs that may explain individuals’ propensity to engage in corrupt behaviour are moral disengagement and belief in a just world. This study aims to investigate the cognitive mechanisms underlying individuals’ intentions to engage in corruption by examining the role that these two variables play. The study employed a quantitative design involving 120 participants. Data was analysed to test the predictive contributions of moral disengagement, as well as the general and personal dimensions of belief in a just world, towards corrupt intentions. The results indicate that moral disengagement significantly predicts corrupt intentions. Furthermore, the two dimensions of belief in a just world exhibit distinct patterns of influence. General belief in a just world was found to be significant in predicting corrupt intentions, whereas personal belief in a just world did not show a significant influence. These findings expand our understanding of the psychological factors underpinning corrupt behaviour and provide important implications for the development of prevention strategies and psychological interventions to reduce the propensity to corruption.